Preventing acute kidney injury during transplantation: the application of novel oxygen carriers. (3rd July 2019) - Thuillier, Raphael; Delpy, Eric; Matillon, Xavier; Kaminski, Jacques; Kasil, Abdelsalam; Soussi, David; Danion, Jerome; Sauvageon, Yse; Rod, Xavier; Donatini, Gianluca; Barrou, Benoit; Badet, Lionel; et al.
ABSTRACT: Introduction : Delayed graft function (DGF) has a significant impact on kidney transplantation outcome. One of the underlying pivotal mechanisms is organ preservation and associated hypothermia and biochemical alteration. Area covered : This paper focuses on organ preservation and its clinical consequences and describes 1. A comprehensive presentation of the pathophysiological mechanism involved in delayed graft function development; 2. The impact on endothelial cells and microvasculature integrity and the consequences on transplanted organ outcome; 3. The reassessment of dynamic organ preservation motivated by the growing use of extended criteria donors and the interest in the potential of normothermia; 4. The role of oxygenation during dynamic preservation; and 5. Novel oxygen carriers and their proof of concept in transplantation, among which M101 (HEMO2 life®) is currently the most extensively investigated. Expert opinion : Metabolic disturbances and imbalance of oxygen supply during preservation highlight the importance of providing oxygen. Normothermia, permitted by recent advances in machine perfusion technology, appears to be the leading edge of preservation technology. Several oxygen transporters are compatible with normothermia; however, only M101 also demonstrates compatibility with standard hypothermic preservation.